2014
DOI: 10.4992/jjpsy.85.13213
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Japanese version of the Autism Spectrum Screening Questionnaire (ASSQ): Development of a short form

Abstract: Hiroyuki Ito (HamamatsuWe examined the psychometric properties of the Japanese version of the Autism Spectrum Screening Questionnaire (ASSQ) and developed a short-form. This study included 157 children with autism spectrum disorders (ASD, ages 7-18, 128 boys) and 4,101 healthy controls (ages 7-15, 3,344 boys) from a general population with a controlled male-female ratio. Four factors (Unusual Interests, Sociality, Peer Relations, and Repetitive Behaviors) were extracted by exploratory factor analysis of contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, a confounding cultural factor is also a possibility. We were not able to discuss this point because mean scores and cut-off scores in domestic studies for school-aged children were not shown [ 43 ]. Third, this study was administered only in a medium-sized city in Japan, thereby limiting its generalizability to other regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a confounding cultural factor is also a possibility. We were not able to discuss this point because mean scores and cut-off scores in domestic studies for school-aged children were not shown [ 43 ]. Third, this study was administered only in a medium-sized city in Japan, thereby limiting its generalizability to other regions.…”
Section: Discussionmentioning
confidence: 99%
“…For the translation process, first, a researcher specializing in special needs education and a child psychiatrist specializing in developmental disorders each independently conducted a translation. Next, those two translations were reviewed by an expert panel arranged by MEXT to check content validity and finalize the Japanese version of the ASSQ [ 42 ], which has been used in clinical settings since 2003, confirming its reliability and validity in Japan [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was translated into the Japanese version by the Ministry of Education, Culture, Sports, Science and Technology with the original authors’ permission [ 15 ]. Its reliability and validity for Japanese populations has also been confirmed [ 16 ]. An ASSQ cut-off score of 13 was shown to discriminate between clinical and nonclinical samples with 91% sensitivity and 77% specificity [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese translation of the high‐functioning version of this measure was used in the current study. It has acceptable psychometric properties (Ito et al, ). The Child Behavior Checklist (CBCL; Achenbach & Rescorla, ) is a 113‐item broadband behavior rating scale that assesses parents’ perceptions of their child's behavior.…”
Section: Methodsmentioning
confidence: 99%